EROSS study: Effect of ovarian reserve on sexual satisfaction - Külahçı Aslan, Elif; Aslan, Kiper; Gürlüler, Jale; Uyanıklar, Özlem; Kılık, Tuğba; Türk, Pınar; Özden, Okan; Kasapoğlu, Işıl; Uncu, Gürkan (Taylor and Francis Ltd., 2022)
The population of this multicenter prospective cohort study comprised 180 women. Women who were admitted to the gynaecology department with any symptoms aged 18-40 years, whose ovarian reserve was tested, were prospectively enrolled in the study. The Female Sexual Function Index (FSFI) survey was administered to all patients. Demographic parameters (age, body mass index), ovarian reserve tests and FSFI scores were analysed. FSFI scores were compared between the patients with diminished ovarian reserve (DOR) and normal ovarian reserve (NOR). Mean women age was 30.8 +/- 5.1 years. Median (with quartiles) AFC was 15 (10-20) and anti-mullerian hormone (AMH) was 2.6 (1.3-4.3) ng/mL. Mean FSFI score was 27 +/- 4.7. The FSFI score was positively correlated with AMH and AFC and negatively correlated with women age. FSFI score depending on ovarian reserve were; 24.7 +/- 5.2 vs. 27.4 +/- 4.3, p < .01 (Respectively; DOR group (n = 43) vs. NOR group (n = 132)). Threshold value for AMH to predict sexual hypofunction was 2.32 with 67% sensitivity - 62% specificity (AUC: 0.68 p < .01) and for AFC to predict sexual hypofunction was 15 with 65% sensitivity - 60% specificity (AUC: 0.67 p < .01). In conclusion, the ovarian reserve should be considered in reproductive aged women while assessing the exact aetiology of female sexual dysfunction. IMPACT STATEMENT What is already known on this subject? Sexual dysfunction is a common disorder and negatively affects the life quality of women. Its estimated prevalence is 40% in women worldwide. There are still unknown aetiologies for sexual dysfunction. What do the results of this study add? The female sexual function index is positively correlated with ovarian reserve. Decreasing sexual functions is related to decreased ovarian reserve. Lower AMH than 2.32 ng/dl and lower antral follicle count than 15 are associated with sexual hypofunction. What are the implications of these findings for clinical practice and/or further research? This pilot study showed the relationship between sexual functions and ovarian reserve. In daily practice, the ovarian reserve should be considered in reproductive-aged women while assessing the exact aetiology of the sexual dysfunction.
Keywords: Anti-Mullerian Hormone; Antral Follicle Count; Female Sexual Function Index; Ovarian Reserve; Sexual Satisfaction